PERENCANAAN LONG STORAGE KEMALANG KABUPATEN KLATEN JAWA TENGAH - Tony Susanto; Muhammad Idu Zaman Suquti; Sriyana Sriyana; Slamet Hargono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
Irrigation water demand and raw water in Klaten regency is increasing in line with population growth. Raw water needs in Klaten regency have been obtained from well water. For the Government in this case the Department of Water Resources Management (PSDA) seeks to develop new sources of raw water by building Kemalang Long Storage. As the rainy season water reservoir, water reservoir can also be efficiently used in the dry season. Design of long storage Kemalang aims to meet the needs of raw water in three districts Karangnongko, Manisrenggo and Kebonarum and irrigation water to irrigate an area of 322 ha. Based on the mainstay discharge analysis by the method of F.J Mock obtained the discharge mainstay minimum of 125 liters/sec. For the body design of the long storage dam used the flood discharge hydrological data HSS Gamma I method with flood discharge plan 50 years return period amounted 43,432 m3/sec. Kemalang Long Storage reservoir volume is 27.235,10 m3. Long storage is planned to supply raw water at 0,138 m3/sec and irrigation water needs by 23 liters/sec/ha. The planned long storage dam 14,5 m high, with a base elevation ponds +348,00 m, +362,5,00 m dam crest elevation, surveillance 1,5 m high, 6 m wide dam crest, upstream slope of 1:3, 1:2,25 downstream slope. In planning this Kemalang Long Storage used Ogee threshold type spillway width 10 m with a height of 1,5 m and a spillway crest elevation of +359,00 m, using an eject pond flat type III with a length of 9,5 m. This project implementation is scheduled for 24 weeks with a budget plan of Rp.5.166.595.000,00.